Genetic variation among methicillin-resistant Staphylococcus aureus isolates from cancer patient in Saudi Arabia - Alreshidi, Mateq Ali; Al-Salamah, Ali A.; Awang Hamat, Rukman; Neela, Vasantha Kumari; Alsharari, Ahmad Subeh; Atshan, Salman Sahab; Alajlan, Hisham H.; Shamsudin, Mariana Nor (Springer Verlag, 2013)
One hundred and twenty methicillin-resistant Staphylococcus aureus (MRSA) isolated from cancer and non-cancer patients in Saudi Arabia were investigated for antibiotic resistance, virulence determinants and genotypes. The majority of MRSA isolates from cancer (n = 44, 73.3 %) and non-cancer patients (n = 34, 56.7 %) were multi-resistant to more than four classes of antibiotics. Virulence gene profiling showed that all strains were commonly positive for adhesin genes, except ebps and bbp genes, which were not detected in any isolate. Although the presence of adhesin genes varied slightly among MRSA isolates from cancer and non-cancer patients, these variations were not found to be statistically significant. In contrast, the presence of the toxin genes seb, sec, seg and sei was significantly elevated in MRSA strains isolated from cancer patients. Multilocus sequence typing (MLST) detected six and nine sequence types (STs) among isolates from cancer and non-cancer patients, respectively. Using spa typing, 12 and 25 types were detected, including four new types. The ability of different MRSA clones to become multi-resistant and their ability to acquire different virulence factors may contribute to their success as pathogens in individual groups of patients.